Life Course, Work, and Labour in Global History - Ehmer, Josef; Lentz, Carola (Work in Global and Historical Perspective, 2023)
This multidisciplinary volume offers unique perspectives on the complexity of the work-life course nexus across the globe and throughout the centuries, reaching from the early modern period to the present day, and from Europe and Africa to India, China, and Japan. Historians, anthropologists, and sociologists reveal the crucial influence of age and gender as well as family and kin on work lives and discuss the impact of current societal change.